Using a cartographic model to assist medical diagnoses - Carvalho, Elizabeth Simão (2008)
Objective The main goal of the CHUB (cartographic human body) model is to introduce a cartographic approach that can assist the analysis, visualization and diagnosis of medical images and related data. Method Acartographic model is proposed as a reference framework for the development of computer systems and applications. This model accommodates subtle spatial features of these data that may facilitate diagnosis. Medical images and related data are structured into different “human-referenced” information layers. Algebraic map operations are used to combine these layers and achieve greater insights into the information content. Results Two case studies were considered to evaluate and validate the model: hydrokinetic therapy and the diagnosis of knee osteoarthritis. A prototype based on the CHUB model was implemented and two different approaches were performed to test and evaluate it. Full acceptance of the model was achieved by clinicians who used the CHUB system.Conclusion Acartographic model provides a feasible means for analyzing and visualizing medical image and related data. CHUB is a suitable model that may be used as a common framework for systems, applications and/or support tools that analyze and visualize medical images and related data (for example, in disease diagnosis).